BIROKRASI DAN KULTUR STRUKTUR RASIONAL-EGALITER: SUMBANGAN AGAMA UNTUK PENGUATAN GOOD GOVERNANCE - Ubaidillah Achmad (Millah: Journal of Religious Studies, 2007)
The role and function of religion recently in the government system seem to have problems because of the believers itself. The fact shows that in the government order that is led by most righteous people, the management indicates various deficiencies, such as inefficiency, authority abuse, collusion, corruption, nepotism, and society’s cooptation to support the political party of the regime. Therefore, to improve the order, it cannot be subjected to the religion believers only, without strengthening the good governance. This last statement requires knowledge, attitude, and action of the public service officials. Furthermore, this is a step of improvement of political abuse, including bad performance of bureaucracy. The article tries to highlight the significant role of religious consciousness relevant to the development of good governance. Good governance will be well -implemented, if each takes part actively, together with government, in developing community’s understanding on the importance of rational-egalitarians in the government system. It is also required a firmness of moral principles and ethic awareness of all public service officials and society to execute the good governance in the government system.